Análise de processos alternativos na preparação de esqueletos para uso didático - da Silveira, Márcio José; Teixeira, Gustavo Monteiro [UNESP]; de Oliveira, Edson Fontes (Universidade Estadual de Maringa, 2008)
Zoology laboratories at institutions of research and education have shown great demand for anatomical parts for practical lessons. However, although the bibliography is not necessarily scarce, analyses of the cost/benefit relations of such processes are rare, considering aspects such as preparation time, quality of the anatomical parts, and material and human resources. In addition to the common techniques already used, new low-cost products, not cited in literature and easily found in the market, were also tested. The main objective of this work was to elaborate and organize information on techniques of bone parts maceration for study collections, making comparative analyses on the cost/benefit relations of each technique. Twelve products were tested, evaluating experimental conditions such as: concentration and combination of reagents, temperature, pH and time of exposure of the parts to the reagents. The results indicated that the products recommended for the use in the maceration processes were: water, hydrogen peroxide and papaya juice (Carica papaya).
Analysis of alternative processes of skeleton preparation for educational uses
Keywords: Hydrogen peroxide; Maceration; Papaya juice; Skeleton clarification